Academia and nihilism: some critical perspectives. - Cohen, Sande (Rethinking History, 2011)
This paper argues that nihilism is not an obsolete cultural and intellectual problem that can be safely left in the past. Nihilism involves processes that are not fully historicized. Some sense of the concept is necessary in order to understand important social selections and acts of power. Using some key works by Deleuze and Nietzsche, this essay argues that nihilism is a way to discuss specific academic processes, including topics of peer-review, scholarly recourse to ideals, and conceptual misrepresentation. The arguments focus on the nihilistic implications of progressive discourse, especially some ideas of Fredric Jameson on cultural studies and knowledge-production in relation to activism. Nihilism, it is argued, involves the political falsification of concepts and is built-in to contemporary contradictions of intellectuals.